2018
DOI: 10.1101/305383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel panel of short mononucleotide repeats linked to informative polymorphisms enabling effective high volume low cost discrimination between mismatch repair deficient and proficient tumours

Abstract: Somatic mutations in mononucleotide repeats are commonly used to assess the mismatch repair status of tumours. Current tests focus on repeats with a length above 15bp, which tend to be somatically more unstable than shorter ones. These longer repeats also have a substantially higher PCR error rate and tests that use capillary electrophoresis for fragment size analysis often require expert interpretation. In this communication, we present a panel of 17 short repeats (length 7–12bp) for sequence-based microsatel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Nineteen and 73 CRC DNAs were provided by the Department of Molecular Pathology, University of Edinburgh, UK, and the Oncogenetics and Hereditary Cancer Group, Complejo Hospitalario de Navarra, Spain, respectively. These 92 samples were residual stocks from Redford et al (). An additional 128 CRC DNAs or CRC formalin‐fixed paraffin‐embedded (FFPE) tissue samples were provided by the Northern Genetics Service, Newcastle Hospitals NHS Foundation Trust, UK.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen and 73 CRC DNAs were provided by the Department of Molecular Pathology, University of Edinburgh, UK, and the Oncogenetics and Hereditary Cancer Group, Complejo Hospitalario de Navarra, Spain, respectively. These 92 samples were residual stocks from Redford et al (). An additional 128 CRC DNAs or CRC formalin‐fixed paraffin‐embedded (FFPE) tissue samples were provided by the Northern Genetics Service, Newcastle Hospitals NHS Foundation Trust, UK.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously used amplicon sequencing of short (7–12 base pairs [bp]), monomorphic MNRs to classify the MSI status of CRCs, without needing matched normal tissue (Redford et al, ). Short MNRs were selected as longer (>15 bp) microsatellites are associated with increased PCR and sequencing error (Fazekas, Steeves, & Newmaster, ), and it has been reported that 9–15 bp microsatellites give the greatest differences in mutation frequencies between MSI‐H and microsatellite stable (MSS) samples using NGS (Maruvka et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 MNRs with length 7-12bp and neighbouring SNP 29 were selected to test for MMR deficiency. BRAF V600E was included to screen for sporadic MMRd CRCs.…”
Section: Marker Selectionmentioning
confidence: 99%
“…The MSI classifier used custom R scripts and the algorithm previously described by Redford et al 29 . In summary, to determine the relative probability that a sample is modelled by an MMRd versus an MMRp phenotype, both the proportion of reads containing microsatellite deletions and the allelic bias of deletions are used.…”
Section: Sequencing Read Analysis and Msi Classificationmentioning
confidence: 99%